Interleukin 18 and associated markers of T helper cell type 1 activity in coeliac disease. Issue 2 (1st February 2002) - Salvati, V M; MacDonald, T T; Bajaj-Elliott, M; Borrelli, M; Staiano, A; Auricchio, S; Troncone, R; Monteleone, G
Abstract : Background: Coeliac disease (CD) is caused by a T helper cell type 1 (Th1) response in the small intestinal mucosa to dietary gluten. Paradoxically, interleukin (IL)-12, the major Th1 inducing factor, is undetectable in the mucosa of active CD. IL-18 is a recently described cytokine capable of promoting T cell interferon (IFN)-γ production and facilitating Th1 cell polarisation. Aim: To examine expression of IL-18 and IL-18-associated Th1 proteins in CD. Methods: IL-18 and IFN-γ RNA transcripts were determined by quantitative reverse transcriptase-polymerase chain reaction (RT-PCR). IL-18 and caspase-1 protein expression were assessed by western blotting. Caspase-1 activity was determined using a commercially available assay. RNA transcripts for the IL-18 receptor subunits, IL-1 receptor related protein (IL-1 Rrp) and accessory protein-like subunit (AcPL), and IL-18 induced Th1 specific T box transcription factor (T-bet) were measured by RT-PCR and Southern blotting. Results: IL-18 RNA transcripts were found in all mucosal samples analysed, with no difference between CD patients and controls. By western blot analysis, a large protein of approximately 24 kDa, corresponding to the immature IL-18, was detected in all mucosal samples from CD patients and controls. In contrast, mature IL-18 was only seen in CD patients. Immunoreactivity corresponding to both immature and mature caspase-1 was present in both CD and control samples. Tissue homogenates from CD patients and controls expressed similar levels of caspase-1 activity. IL-1Rrp and AcPL were seen in all samples but were expressed at greater levels in the mucosa of CD patients. T-bet was also upregulated in CD. Conclusions: Active IL-18 is expressed in CD as well as other markers of Th1 polarisation.